2021
DOI: 10.1590/acb360607
|View full text |Cite
|
Sign up to set email alerts
|

Changes of renal histopathology and the role of Nrf2/HO-1 in asphyxial cardiac arrest model in rats

Abstract: To investigate the role of Nrf2/HO-1 in renal histopathological ailments time-dependently in asphyxial cardiac arrest (CA) rat model. Methods: Eighty-eight Sprague Dawley male rats were divided into five groups of eight rats each. Asphyxial CA was induced in all the experimental rats except for the sham group. The rats were sacrificed at 6 hours, 12 hours, one day and two days post-CA. Serum blood urea nitrogen (BUN), creatinine (Crtn) and malondialdehyde from the renal tissues were evaluated. Hematoxylin and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
(47 reference statements)
3
4
0
Order By: Relevance
“…Increased ROS can also lead to MDA generation and severely weaken the antioxidant enzyme system ( 37 ). In the present study, MDA was markedly increased in CA groups compared with the sham group, resembling results of a previous study ( 26 ). Thus, asphyxial CA can increase oxidative stress in a time-dependent manner and provoke renal damage.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Increased ROS can also lead to MDA generation and severely weaken the antioxidant enzyme system ( 37 ). In the present study, MDA was markedly increased in CA groups compared with the sham group, resembling results of a previous study ( 26 ). Thus, asphyxial CA can increase oxidative stress in a time-dependent manner and provoke renal damage.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, the survival rate declined in a time-dependent manner, reaching 33% at two days post-CA. Previous studies have also shown the same pattern of survivability ( 25 , 26 ). Therefore, our asphyxial CA model was suitable for studying CA patients.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Recently, it has been suggested that Nrf2/HO-1 pathway was activated in the early stage after ROSC. However, the expression of Nrf2/HO-1 decreased, the renal injury and dysfunction increased, and the survival rate of rats decreased during later stage after ROSC ( 50 ). Therefore, the activation of Nrf2/HO-1 pathway may be a promising therapeutic target on post-resuscitation AKI.…”
Section: Discussionmentioning
confidence: 99%